2017
DOI: 10.1177/1359104516687612
|View full text |Cite
|
Sign up to set email alerts
|

‘How I Feel About My School’: The construction and validation of a measure of wellbeing at school for primary school children

Abstract: There is a growing focus on child wellbeing and happiness in schools, but we lack self-report measures for very young children. Three samples (N = 2345) were combined to assess the psychometric properties of the How I Feel About My School (HIFAMS) questionnaire, which was designed for children aged 4-8 years. Test re-test reliability was moderate (intraclass correlation coefficient = 0.62). HIFAMS assessed a single concept and had moderate internal consistency (Cronbach's alpha values from 0.62 to 0.67). There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…Children completed the How I Feel About My School measure (HIFAMS: Allen et al , 2017) which measures children's attitudes towards school; possible scores range from 0 to 14 (summed across seven items each scored from 0 to 2), with higher scores indicating greater happiness at school.…”
Section: Methodsmentioning
confidence: 99%
“…Children completed the How I Feel About My School measure (HIFAMS: Allen et al , 2017) which measures children's attitudes towards school; possible scores range from 0 to 14 (summed across seven items each scored from 0 to 2), with higher scores indicating greater happiness at school.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate greater happiness at school (range 0–14). Allen et al () found that HIFAMS demonstrated adequate 2‐week test–retest reliability [Spearman's correlation ( r s ) = 0.62; 95% CI: 0.54 to 0.69] and moderate internal consistency (Cronbach's α = 0.62).…”
Section: Methodsmentioning
confidence: 99%
“…HIFAMS was developed for the STARS trial and has demonstrated validity and moderate reliability among children as young as 4 years when tested in this and two other samples. 52 It has now been translated into Italian and Persian and is being used in several education-based studies in the UK. Our findings would not suggest that being taught by a TCM-trained teacher leaves children happier about their school, but, equally, the study was not powered to detect an effect using this measure.…”
Section: Discussionmentioning
confidence: 99%
“…Children completed the How I Feel About My School (HIFAMS), 52 which measures children's attitudes towards school, with higher scores indicating greater happiness. The HIFAMS is a 7-item measure of a child's attitude towards school, with scores ranging from a possible 0 to 14 (summed across seven items each scored from 0 to 2).…”
Section: How I Feel About My School (Child Completed)mentioning
confidence: 99%